(untitled) (SUNGKAI: Jurnal Aqidah dan Filsafat Islam, 2023)
The Javanese Tedhak Siten tradition is a ceremony for children aged 7-8 months to introduce children to the earth by setting their feet on the ground. This tradition is the result of a combination of Islam and Javanese culture, which is called Javanese-Islamic acculturation. The purpose of this study is to find out the history of the process of implementing the Tedhak Siten Tradition in Muara Sabak Ulu Village, East Tanjung Jabung Regency. Then to find out the purpose and benefits of the Tedhak Siten Tradition in Javanese Society and Understanding the Perspective of Islamic Aqidah towards the Tedhak Siten tradition of the Javanese Community in Muara Sabak Ulu Village, East Tanjung Jabung Regency. This research is included in field research (faild research) using qualitative research methods and phenomenological approaches. The result of this study is that the authors found that the Tedhak Siten tradition in Muara Sabak Ulu Village is a hereditary tradition that is still being preserved by the surrounding community. In Islam the position of aqidah is very important, even though this tradition is thick with Javanese nuances it does not deviate from Islamic aqeedah because in its implementation many Islamic teachings are integrated into this tradition, such as: reading tahlil, praying, giving alms, and gathering. In addition, with this tradition, parents put their hope in Allah SWT so that one day their children will become human beings who are useful for religion, homeland and nation.